A kind of stone material for building decoration and its production process

By combining modified epoxy resin with polyurethane adhesive and mixed stone, the problem of insufficient adhesion and toughness of existing artificial stone adhesives is solved, and antibacterial properties are improved by silicon-containing diisocyanate oligomers, achieving high-quality stone preparation for building decoration.

CN119430740BActive Publication Date: 2025-04-08JIANGSU HUAHUI ARCHITECTURAL DECORATION ENG CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510045838.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-13
Publication Date
2025-04-08
Estimated Expiration
2045-01-13

AI Technical Summary

Technical Problem

Among the existing artificial stone adhesives, unsaturated resins have low adhesion and poor permeability, while epoxy resins have high brittleness and low toughness, resulting in poor quality of finished products. In addition, antibacterial agents are expensive and have few sources, making them difficult to widely promote.

Method used

Using a modified epoxy resin as an adhesive, a modified epoxy resin was used to obtain p-allyl phenol glycidyl ether by reacting epoxy with p-allyl phenol, and reacting with 1,1,1,3,5,5,5-heptamethyltrisiloxane to obtain silicone modified p-allyl phenol glycidyl ether. Then, 5,5-dimethylhein is reacted with the silicone modified product to form a silicon-containing diisocyanate oligomer, and a modified epoxy resin is formed by combining the epoxy resin. The modified epoxy resin is mixed with polyurethane adhesive and mixed stone, and after vibration pressing and curing treatment, the stone for building decoration is produced.

Benefits of technology

It improves the antibacterial and mechanical properties of epoxy resin, enhances the toughness and impact resistance of stone, improves the adhesive properties and the overall quality of stone.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present invention relates to the field of stone materials for building decoration, specifically a kind of stone material for building decoration and its production process. The present invention mixes marble, quartz stone, granite, pebbles and rutile, and obtains mixed stone after crushing and sieving; epichlorohydrin and p-allylphenol are used as raw materials, 1,1,1,3,5,5,5-heptamethyltrisiloxane and 5,5-dimethylhydantoin are grafted after reaction, and then isophorone diisocyanate is added for polymerization to obtain silicon-containing oligomers; silicon-containing oligomers are mixed with epoxy resin to obtain modified epoxy resin; mixed stone, polyurethane and modified epoxy resin are mixed, after vibration pressing and temperature curing, mold opening, grinding and polishing are obtained to obtain stone plate for building decoration; the stone material for building decoration prepared by the present invention has both good mechanical properties and antibacterial properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of building decoration stone materials, in particular to a building decoration stone material and a production process thereof. Background Art

[0002] Stone used for architectural decoration refers to the stone used as finishing material on buildings, including two categories: natural stone and artificial stone. Compared with natural stone, artificial stone has the advantages of light weight, low radioactivity, bright colors, and high finish. Artificial stone is usually made by mixing natural marble or inorganic powders such as calcite, dolomite, silica sand, glass powder, etc. with resin adhesives, and is formed and solidified by vibration compression, extrusion, etc. It is a green and environmentally friendly building material product and a modern building finishing material that is deeply loved by consumers.

[0003] In the prior art, the adhesives used for artificial stone are unsaturated resins, epoxy resins, etc. Among them, unsaturated resins have low bonding and poor permeability, while epoxy resins are brittle and have low toughness, and are prone to cracking during the pressing process, resulting in poor quality of the finished product. In addition, in the past, inorganic materials such as nano-silver and nano-zinc oxide were commonly used as antibacterial agents in artificial stone. Inorganic antibacterial materials are expensive and have few sources, making them difficult to be widely promoted and used in stone. Summary of the invention

[0004] The object of the present invention is to provide a stone material for architectural decoration and a production process thereof to solve the problems raised in the above background technology.

[0005] In order to solve the above technical problems, the present invention provides the following technical solutions: a stone material for building decoration and a production process thereof, comprising the following steps:

[0006] Step 1:

[0007] S11: epichlorohydrin and p-allylphenol are mixed, 1-1.5% of the total mass of the reactants is added as a benzyltriethylammonium chloride catalyst, and the mixture is stirred at 80-90°C for 5-6 hours under nitrogen protection, then cooled to 50-60°C, and a 30% sodium hydroxide solution is added, and the sodium hydroxide solution is added within 1 hour, and the reaction is continued for 4-5 hours, and the generated sodium chloride is removed by filtration, and the filtrate is washed with deionized water at 60-70°C, and the excess epichlorohydrin is removed by vacuum rotary evaporation, and methanol is added to cool and recrystallize, and finally vacuum dried at 30-40°C for 8-10 hours to obtain p-allylphenol glycidyl ether;

[0008] S12: p-allylphenol glycidyl ether and 1,1,1,3,5,5,5-heptamethyltrisiloxane are mixed and dispersed in anhydrous toluene, and chloroplatinic acid-isopropanol solution is used as a catalyst, and the temperature is raised to 100-110° C. for reaction for 3-5 hours to obtain organosilicon-modified p-allylphenol glycidyl ether;

[0009] S13: 5,5-dimethylhydantoin and organosilicon-modified p-allylphenol glycidyl ether are mixed, reacted at 70-80°C for 2-3h with lithium chloride as a catalyst, and distilled under reduced pressure to obtain organosilicon-grafted dimethylhydantoin, and the organosilicon-grafted dimethylhydantoin is mixed with isophorone diisocyanate, reacted at 60-70°C for 3-5h with dibutyltin dilaurate as a catalyst to obtain a silicon-containing diisocyanate oligomer;

[0010] Step 2:

[0011] S21: mixing an epoxy resin and a silicon-containing diisocyanate oligomer to obtain a modified epoxy resin;

[0012] S22: marble, quartz, granite, pebbles and rutile are mixed, crushed and sieved to obtain coarse stones with a particle size of 50-80 meshes and fine stones with a particle size of 120-150 meshes; the coarse stones and fine stones are mixed in a mass ratio of 1:1 to obtain mixed stones;

[0013] S23: The polyurethane adhesive, modified epoxy resin, epoxy resin curing agent and mixed stone are stirred and evenly mixed, and then poured into a mold, placed for 24 to 30 hours, and vibrated and pressed at 90 to 100 KPa with a vibration frequency of 40 to 50 Hz; then cured at 100 to 120° C. for 1 to 2 hours, and cured at 120 to 150° C. for 1 to 2 hours, and polished after opening the mold to obtain a stone for architectural decoration.

[0014] Furthermore, in S11, the molar ratio of allylphenol, epichlorohydrin and sodium hydroxide is 1:3:(2~2.5).

[0015] Furthermore, in S12, p-allylphenol glycidyl ether and 1,1,1,3,5,5,5-heptamethyltrisiloxane are mixed in a molar ratio of 1:1.

[0016] Furthermore, in S13, 5,5-dimethylhydantoin and silicone-modified p-allylphenol glycidyl ether are mixed in a molar ratio of 1:2.

[0017] Furthermore, in S13, the reaction product of 5,5-dimethylhydantoin and silicone-modified p-allylphenol glycidyl ether is mixed with isophorone diisocyanate at a molar ratio of hydroxyl group to isocyanate group of 1:(1.5-1.8).

[0018] Furthermore, in S21, the contents of the components in the modified epoxy resin are, by weight percentage, 88-93% epoxy resin and 7-12% silicon-containing diisocyanate oligomer.

[0019] Furthermore, in S22, the contents of the components in the mixed stone are, by weight, 70-75 parts of marble, 15-22 parts of quartz, 13-18 parts of granite, 11-17 parts of pebbles, and 6-10 parts of rutile.

[0020] Furthermore, in S23, the amount of each component, by weight, is 16-25 parts of polyurethane adhesive, 50-80 parts of modified epoxy resin, 30-56 parts of epoxy resin curing agent, and 340-470 parts of mixed stone.

[0021] Compared with the prior art, the beneficial effects achieved by the present invention are as follows: the present invention mixes marble, quartz stone, granite, pebbles and rutile, and obtains coarse stone and fine stone by crushing and screening; the coarse stone and the fine stone are mixed in a mass ratio of 1:1 to obtain mixed stone; the mixed stone is mixed with an adhesive, and the mixed stone is vibrated, pressed, solidified, polished and grinded to obtain stone for architectural decoration.

[0022] The adhesive used in the present invention is a mixture of modified epoxy resin and polyurethane adhesive, wherein the modified epoxy resin is a mixture of silicon-containing diisocyanate oligomer and epoxy resin. When preparing the silicon-containing diisocyanate oligomer, the present invention uses epichlorohydrin and p-allylphenol as raw materials to react to obtain p-allylphenol glycidyl ether; then the p-allylphenol glycidyl ether is reacted with 1,1,1,3,5,5,5-heptamethyltrisiloxane to obtain silicone-modified p-allylphenol glycidyl ether; then 5,5-dimethylhydantoin and silicone-modified p-allylphenol glycidyl ether are reacted in a molar ratio of 1:2, and the amino group in the 5,5-dimethylhydantoin reacts with the epoxy group to generate a hydroxyl group, which can be polymerized with isophorone diisocyanate to obtain the silicon-containing diisocyanate oligomer; the silicon-containing diisocyanate oligomer has an antibacterial effect, and after being mixed with an epoxy resin, the antibacterial property of the epoxy resin can be improved; the silicon-containing diisocyanate oligomer is terminated with an isocyanate group, and after reacting with the hydroxyl group on the epoxy resin, a chemical connection is generated to achieve the effect of toughening modification. The organosilicon groups in the oligomers provide steric hindrance, reduce entanglement between epoxy resin segments, keep the epoxy resin at a low viscosity, and facilitate uniform mixing of the adhesive with other components. The oligomers contain carbamate groups generated by the reaction of hydroxyl groups and isocyanate groups, so the modified epoxy resin has good compatibility with polyurethane. The two are mixed and cured to form an interpenetrating network structure, which effectively makes up for the shortcomings of epoxy resin after curing, such as high brittleness and poor toughness, and thus improves the mechanical properties of the stone.

[0023] It should be noted that when preparing silicon-containing diisocyanate oligomers, the researchers believed that when the molar ratio of hydroxyl to isocyanate groups was 1:1, the two would theoretically polymerize infinitely. Therefore, when the molar ratio of hydroxyl to isocyanate groups is closer to 1:1, the larger the polymer molecular weight, and the stronger the steric hindrance effect of the macromolecular polymer, the access to the epoxy resin side chain will have an adverse effect on the subsequent curing and cross-linking of the epoxy resin main chain, resulting in poor modification effect. In the actual research and development process, the researchers also found that it was impossible to obtain a product with relatively uniform molecular weight at this feed ratio. The product not only contained macromolecular polymers, but also small molecular oligomers and a small amount of unreacted reactants. If it was directly blended with the epoxy resin without separation, the expected modification effect could not be achieved. Through continuous experiments, it was found that when silicone-grafted dimethylhydantoin and isophorone diisocyanate were added at a molar ratio of hydroxyl group to isocyanate group of 1: (1.5~1.8), oligomers with relatively uniform molecular chain segment length could be obtained, and the modification effect on epoxy resin was stable and controllable. DETAILED DESCRIPTION

[0024] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0025] Materials and sources used in the present invention: polyurethane adhesive comes from 3M Company, item number EC-3532; industrial grade bisphenol A epoxy resin 128 comes from the epoxy resin plant of Nanya Electronic Materials (Kunshan) Co., Ltd.; epoxy resin curing agent is triethylenetetramine, which comes from Jinan Century Tongda Chemical Co., Ltd.

[0026] Embodiment 1: A stone material for building decoration and a production process thereof, comprising the following steps:

[0027] Step 1:

[0028] S11: epichlorohydrin and p-allylphenol are mixed, benzyltriethylammonium chloride catalyst of 1.5% of the total mass of the reactants is added, and the mixture is stirred at 80°C for 5 hours under nitrogen protection, then cooled to 50°C, and a sodium hydroxide solution of 30% by mass is added, and the sodium hydroxide solution is added within 1 hour, and the reaction is continued for 4 hours, and the generated sodium chloride is removed by filtration, and the filtrate is washed with deionized water at 60°C, and the excess epichlorohydrin is removed by vacuum rotary evaporation, and methanol is added to cool and recrystallize, and finally dried at 30°C in vacuum for 8 hours to obtain p-allylphenol glycidyl ether; wherein the molar ratio of p-allylphenol, epichlorohydrin and sodium hydroxide is 1:3:2;

[0029] S12: p-allylphenol glycidyl ether and 1,1,1,3,5,5,5-heptamethyltrisiloxane are mixed in a molar ratio of 1:1 and dispersed in anhydrous toluene, and chloroplatinic acid-isopropanol solution is used as a catalyst, and the temperature is raised to 100° C. for reaction for 3 hours to obtain organosilicon-modified p-allylphenol glycidyl ether;

[0030] S13: 5,5-dimethylhydantoin and organosilicon-modified p-allylphenol glycidyl ether are mixed in a molar ratio of 1:2, reacted at 70-80°C for 2-3h with lithium chloride as a catalyst, and distilled under reduced pressure to obtain organosilicon-grafted dimethylhydantoin, and organosilicon-grafted dimethylhydantoin is mixed with isophorone diisocyanate in a molar ratio of hydroxyl group to isocyanate group of 1:1.5, reacted at 60°C for 3h with dibutyltin dilaurate as a catalyst, and obtained a silicon-containing diisocyanate oligomer;

[0031] Step 2:

[0032] S21: Mixing 93% epoxy resin and 7% silicon-containing diisocyanate oligomer by weight to obtain a modified epoxy resin;

[0033] S22: 75 kg of marble, 22 kg of quartz, 18 kg of granite, 17 kg of pebbles, and 10 kg of rutile are mixed, crushed, and sieved to obtain coarse stone with a particle size of 50 mesh and fine stone with a particle size of 120 mesh; the coarse stone and the fine stone are mixed in a mass ratio of 1:1 to obtain a mixed stone;

[0034] S23: 19 kg of polyurethane adhesive, 63 kg of modified epoxy resin, 43 kg of epoxy resin curing agent and 390 kg of mixed stone are stirred and evenly mixed, poured into a mold, left for 24 hours, and vibrated and pressed at 90 KPa with a vibration frequency of 40 Hz; then cured at 100 ° C for 1 hour and at 120 ° C for 1 hour, and polished after opening the mold to obtain a stone for architectural decoration.

[0035] Embodiment 2: A stone material for building decoration and a production process thereof, comprising the following steps:

[0036] Step 1:

[0037] S11: epichlorohydrin and p-allylphenol are mixed, benzyltriethylammonium chloride catalyst of 1.5% of the total mass of the reactants is added, and the mixture is stirred at 85°C for 5.5h under nitrogen protection, then cooled to 55°C, and a sodium hydroxide solution of 30% by mass is added, and the sodium hydroxide solution is added within 1h, and the reaction is continued for 4.5h, and the generated sodium chloride is removed by filtration, and the filtrate is washed with deionized water at 65°C, and the excess epichlorohydrin is removed by vacuum rotary evaporation, and methanol is added to cool and recrystallize, and finally dried at 30°C in vacuum for 8h to obtain p-allylphenol glycidyl ether; wherein the molar ratio of p-allylphenol, epichlorohydrin and sodium hydroxide is 1:3:2;

[0038] S12: p-allylphenol glycidyl ether and 1,1,1,3,5,5,5-heptamethyltrisiloxane are mixed in a molar ratio of 1:1 and dispersed in anhydrous toluene, and chloroplatinic acid-isopropanol solution is used as a catalyst, and the temperature is raised to 105° C. for reaction for 4 hours to obtain organosilicon-modified p-allylphenol glycidyl ether;

[0039] S13: 5,5-dimethylhydantoin and organosilicon-modified p-allylphenol glycidyl ether were mixed in a molar ratio of 1:2, reacted at 75°C for 2.5 hours with lithium chloride as a catalyst, and distilled under reduced pressure to obtain organosilicon-grafted dimethylhydantoin, and organosilicon-grafted dimethylhydantoin was mixed with isophorone diisocyanate in a molar ratio of hydroxyl group to isocyanate group of 1:1.6, reacted at 65°C for 3.5 hours with dibutyltin dilaurate as a catalyst, and obtained a silicon-containing diisocyanate oligomer;

[0040] Step 2:

[0041] S21: Mixing 90% of epoxy resin and 10% of silicon-containing diisocyanate oligomer by weight to obtain a modified epoxy resin;

[0042] S22: 75 kg of marble, 22 kg of quartz, 18 kg of granite, 17 kg of pebbles, and 10 kg of rutile are mixed, crushed, and sieved to obtain coarse stone with a particle size of 50 mesh and fine stone with a particle size of 120 mesh; the coarse stone and the fine stone are mixed in a mass ratio of 1:1 to obtain a mixed stone;

[0043] S23: 19 kg of polyurethane adhesive, 63 kg of modified epoxy resin, 43 kg of epoxy resin curing agent and 390 kg of mixed stone are stirred and evenly mixed, poured into a mold, left for 28 hours, and vibrated and pressed at 95 KPa with a vibration frequency of 45 Hz; then cured at 115 ° C for 1.5 hours and at 135 ° C for 1.5 hours, and polished after opening the mold to obtain a stone for architectural decoration.

[0044] Embodiment 3: A stone material for building decoration and a production process thereof, comprising the following steps:

[0045] Step 1:

[0046] S11: epichlorohydrin and p-allylphenol are mixed, benzyltriethylammonium chloride catalyst of 1.5% of the total mass of the reactants is added, and the mixture is stirred at 90°C for 6 hours under nitrogen protection, then cooled to 60°C, and a sodium hydroxide solution of 30% by mass is added, and the sodium hydroxide solution is added within 1 hour, and the reaction is continued for 5 hours, and the generated sodium chloride is removed by filtration, and the filtrate is washed with deionized water at 70°C, and the excess epichlorohydrin is removed by vacuum rotary evaporation, and methanol is added to cool and recrystallize, and finally dried at 30°C in vacuum for 8 hours to obtain p-allylphenol glycidyl ether; wherein the molar ratio of p-allylphenol, epichlorohydrin and sodium hydroxide is 1:3:2;

[0047] S12: p-allylphenol glycidyl ether and 1,1,1,3,5,5,5-heptamethyltrisiloxane are mixed in a molar ratio of 1:1 and dispersed in anhydrous toluene, and chloroplatinic acid-isopropanol solution is used as a catalyst, and the temperature is raised to 110° C. for reaction for 5 hours to obtain organosilicon-modified p-allylphenol glycidyl ether;

[0048] S13: 5,5-dimethylhydantoin and organosilicon-modified p-allylphenol glycidyl ether were mixed in a molar ratio of 1:2, reacted at 80°C for 3 hours with lithium chloride as a catalyst, and distilled under reduced pressure to obtain organosilicon-grafted dimethylhydantoin, and organosilicon-grafted dimethylhydantoin was mixed with isophorone diisocyanate in a molar ratio of hydroxyl group to isocyanate group of 1:1.8, reacted at 70°C for 5 hours with dibutyltin dilaurate as a catalyst, and obtained a silicon-containing diisocyanate oligomer;

[0049] Step 2:

[0050] S21: 88% of epoxy resin and 12% of silicon-containing diisocyanate oligomer are mixed by weight to obtain a modified epoxy resin;

[0051] S22: 75 kg of marble, 22 kg of quartz, 18 kg of granite, 17 kg of pebbles, and 10 kg of rutile are mixed, crushed, and sieved to obtain coarse stone with a particle size of 50 mesh and fine stone with a particle size of 120 mesh; the coarse stone and the fine stone are mixed in a mass ratio of 1:1 to obtain a mixed stone;

[0052] S23: 19 kg of polyurethane adhesive, 63 kg of modified epoxy resin, 43 kg of epoxy resin curing agent and 390 kg of mixed stone are stirred and evenly mixed, poured into a mold, left for 30 hours, and vibrated and pressed at 100 KPa with a vibration frequency of 50 Hz; then cured at 120°C for 2 hours and at 150°C for 2 hours, and polished after opening the mold to obtain a stone for architectural decoration.

[0053] Comparative Example 1: No silicon-containing diisocyanate oligomer is added to modify the epoxy resin, and the other parameters are the same as those in Example 1.

[0054] S1: 75 kg of marble, 22 kg of quartz, 18 kg of granite, 17 kg of pebbles and 10 kg of rutile are mixed, crushed and sieved to obtain coarse stone with a particle size of 50 mesh and fine stone with a particle size of 120 mesh; the coarse stone and the fine stone are mixed in a mass ratio of 1:1 to obtain mixed stone;

[0055] S2: 19kg of polyurethane adhesive, 63kg of modified epoxy resin, 43kg of epoxy resin curing agent and 390kg of mixed stone are stirred and evenly mixed, then poured into a mold, left for 24 hours, and vibrated and pressed at 90Kpa with a vibration frequency of 40Hz; then cured at 100°C for 1h and at 120°C for 1h, and polished after opening the mold to obtain stone for architectural decoration.

[0056] Comparative Example 2: No polyurethane adhesive was added, and the other parameters were the same as those in Example 2.

[0057] Step 1:

[0058] S11: epichlorohydrin and p-allylphenol are mixed, benzyltriethylammonium chloride catalyst of 1.5% of the total mass of the reactants is added, and the mixture is stirred at 85°C for 5.5h under nitrogen protection, then cooled to 55°C, and a sodium hydroxide solution of 30% by mass is added, and the sodium hydroxide solution is added within 1h, and the reaction is continued for 4.5h, and the generated sodium chloride is removed by filtration, and the filtrate is washed with deionized water at 65°C, and the excess epichlorohydrin is removed by vacuum rotary evaporation, and methanol is added to cool and recrystallize, and finally dried at 30°C in vacuum for 8h to obtain p-allylphenol glycidyl ether; wherein the molar ratio of p-allylphenol, epichlorohydrin and sodium hydroxide is 1:3:2;

[0059] S12: p-allylphenol glycidyl ether and 1,1,1,3,5,5,5-heptamethyltrisiloxane are mixed in a molar ratio of 1:1 and dispersed in anhydrous toluene, and chloroplatinic acid-isopropanol solution is used as a catalyst, and the temperature is raised to 105° C. for reaction for 4 hours to obtain organosilicon-modified p-allylphenol glycidyl ether;

[0060] S13: 5,5-dimethylhydantoin and organosilicon-modified p-allylphenol glycidyl ether were mixed in a molar ratio of 1:2, reacted at 75°C for 2.5 hours with lithium chloride as a catalyst, and distilled under reduced pressure to obtain organosilicon-grafted dimethylhydantoin, and organosilicon-grafted dimethylhydantoin was mixed with isophorone diisocyanate in a molar ratio of hydroxyl group to isocyanate group of 1:1.6, reacted at 65°C for 3.5 hours with dibutyltin dilaurate as a catalyst, and obtained a silicon-containing diisocyanate oligomer;

[0061] Step 2:

[0062] S21: Mixing 90% of epoxy resin and 10% of silicon-containing diisocyanate oligomer by weight to obtain a modified epoxy resin;

[0063] S22: 75 kg of marble, 22 kg of quartz, 18 kg of granite, 17 kg of pebbles, and 10 kg of rutile are mixed, crushed, and sieved to obtain coarse stone with a particle size of 50 mesh and fine stone with a particle size of 120 mesh; the coarse stone and the fine stone are mixed in a mass ratio of 1:1 to obtain a mixed stone;

[0064] S23: 63 kg of modified epoxy resin, 43 kg of epoxy resin curing agent and 390 kg of mixed stone are stirred and mixed evenly, poured into a mold, left for 28 hours, and vibrated and pressed at 95 KPa with a vibration frequency of 45 Hz; then cured at 115 ° C for 1.5 hours and at 135 ° C for 1.5 hours, and polished after opening the mold to obtain a stone for architectural decoration.

[0065] Comparative Example 3: The reaction product in S13 was mixed with isophorone diisocyanate at a molar ratio of hydroxyl group to isocyanate group of 1:1, and the other parameters were the same as those in Example 3.

[0066] Step 1:

[0067] S11: epichlorohydrin and p-allylphenol are mixed, benzyltriethylammonium chloride catalyst of 1.5% of the total mass of the reactants is added, and the mixture is stirred at 90°C for 6 hours under nitrogen protection, then cooled to 60°C, and a sodium hydroxide solution of 30% by mass is added, and the sodium hydroxide solution is added within 1 hour, and the reaction is continued for 5 hours, and the generated sodium chloride is removed by filtration, and the filtrate is washed with deionized water at 70°C, and the excess epichlorohydrin is removed by vacuum rotary evaporation, and methanol is added to cool and recrystallize, and finally dried at 30°C in vacuum for 8 hours to obtain p-allylphenol glycidyl ether; wherein the molar ratio of p-allylphenol, epichlorohydrin and sodium hydroxide is 1:3:2;

[0068] S12: p-allylphenol glycidyl ether and 1,1,1,3,5,5,5-heptamethyltrisiloxane are mixed in a molar ratio of 1:1 and dispersed in anhydrous toluene, and chloroplatinic acid-isopropanol solution is used as a catalyst, and the temperature is raised to 110° C. for reaction for 5 hours to obtain organosilicon-modified p-allylphenol glycidyl ether;

[0069] S13: 5,5-dimethylhydantoin and organosilicon-modified p-allylphenol glycidyl ether are mixed in a molar ratio of 1:2, reacted at 80°C for 3 hours with lithium chloride as a catalyst, and distilled under reduced pressure to obtain organosilicon-grafted dimethylhydantoin, and organosilicon-grafted dimethylhydantoin is mixed with isophorone diisocyanate in a molar ratio of hydroxyl group to isocyanate group of 1:1, reacted at 70°C for 5 hours with dibutyltin dilaurate as a catalyst, and obtained a silicon-containing diisocyanate polymer;

[0070] Step 2:

[0071] S21: Mixing 88% of epoxy resin and 12% of silicon-containing diisocyanate polymer by weight to obtain a modified epoxy resin;

[0072] S22: 75 kg of marble, 22 kg of quartz, 18 kg of granite, 17 kg of pebbles, and 10 kg of rutile are mixed, crushed, and sieved to obtain coarse stone with a particle size of 50 mesh and fine stone with a particle size of 120 mesh; the coarse stone and the fine stone are mixed in a mass ratio of 1:1 to obtain a mixed stone;

[0073] S23: 19 kg of polyurethane adhesive, 63 kg of modified epoxy resin, 43 kg of epoxy resin curing agent and 390 kg of mixed stone are stirred and evenly mixed, poured into a mold, left for 30 hours, and vibrated and pressed at 100 KPa with a vibration frequency of 50 Hz; then cured at 120°C for 2 hours and at 150°C for 2 hours, and polished after opening the mold to obtain a stone for architectural decoration.

[0074] Experiment: The performance of the architectural decorative stones prepared in Examples 1 to 3 and Comparative Examples 1 to 3 was tested, and the experimental results are shown in the following table.

[0075] Mechanical properties: The samples were made into stone slabs with a size of 150mm×100mm×15mm, and the performance of the samples was tested using a strength testing machine at a rate of 0.8mm / min. The impact test was performed on the samples with a notch depth of 2mm using a steel ball weighing 50kg to test the impact strength.

[0076] Antibacterial performance test: The test was carried out according to the method in standard JC / T 897-2014, and Escherichia coli was used as the test bacteria.

[0077]

[0078] Conclusion: The data of Examples 1 to 3 show that the stone for architectural decoration prepared by the present invention has good mechanical properties. The data of Example 1 and Comparative Example 1 show that after adding the silicon-containing diisocyanate oligomer, the antibacterial and mechanical properties of the stone slab are improved; the data of Example 2 and Comparative Example 2 show that the addition of polyurethane can improve the mechanical properties of the stone; the data of Example 3 and Comparative Example 3 show that the silicon-containing diisocyanate oligomer prepared at different feed ratios has different modification effects on epoxy resin. When the feed is made according to the molar ratio of hydroxyl group to isocyanate group of 1:1, the modification effect of the reaction product on epoxy resin is poor, and the performance of the stone finally obtained is poor.

[0079] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a stone material for architectural decoration, characterized in that: The following steps are involved: S1: Marble, quartz, granite, pebbles and rutile are mixed, crushed and sieved to obtain coarse stone and fine stone, and the coarse stone and fine stone are mixed to obtain mixed stone; S2: The polyurethane adhesive, modified epoxy resin, epoxy resin curing agent and mixed stone are stirred and mixed evenly, and then poured into a mold, placed for 24-30 hours, and vibrated and pressed at 90-100Kpa with a vibration frequency of 40-50Hz; then cured at 100-120°C for 1-2 hours, and cured at 120-150°C for 1-2 hours, and polished after mold opening to obtain a stone for architectural decoration; wherein, in the modified epoxy resin, the content of each component, by weight percentage, is 88-93% epoxy resin and 7-12% silicon-containing diisocyanate oligomer; the preparation method of the silicon-containing diisocyanate oligomer comprises the following steps: Step 1: epichlorohydrin and p-allylphenol are mixed, benzyltriethylammonium chloride catalyst of 1-1.5% of the total mass of the reactants is added, stirred at 80-90°C for 5-6h under nitrogen protection, then cooled to 50-60°C, 30% sodium hydroxide solution is added, and the sodium hydroxide solution is added within 1h, and the reaction is continued for 4-5h, and the generated sodium chloride is removed by filtration, and the filtrate is washed with deionized water at 60-70°C, and the excess epichlorohydrin is removed by vacuum rotary evaporation, methanol is added to cool and recrystallize, and finally vacuum dried at 30-40°C for 8-10h to obtain p-allylphenol glycidyl ether; Step 2: p-allylphenol glycidyl ether and 1,1,1,3,5,5,5-heptamethyltrisiloxane are mixed and dispersed in anhydrous toluene, and chloroplatinic acid-isopropanol solution is used as a catalyst, and the temperature is raised to 100-110° C. for reaction for 3-5 hours to obtain organosilicon-modified p-allylphenol glycidyl ether; Step 3: 5,5-dimethylhydantoin and organosilicon-modified p-allylphenol glycidyl ether are mixed, lithium chloride is used as a catalyst, the mixture is reacted at 70-80° C. for 2-3 hours, and reduced pressure distillation is performed to obtain organosilicon-grafted dimethylhydantoin. The organosilicon-grafted dimethylhydantoin is mixed with isophorone diisocyanate, dibutyltin dilaurate is used as a catalyst, the mixture is reacted at 60-70° C. for 3-5 hours, and a silicon-containing diisocyanate oligomer is obtained; In step 3, the organosilicon-grafted dimethyl hydantoin is mixed with isophorone diisocyanate in a molar ratio of hydroxyl group to isocyanate group of 1:(1.5-1.8).

2. The method for preparing a stone material for architectural decoration according to claim 1, characterized in that: In S1, the amount of each component, by weight, is 70-75 parts of marble, 15-22 parts of quartz, 13-18 parts of granite, 11-17 parts of pebbles, and 6-10 parts of rutile; in the mixed stone, the mass ratio of coarse stone to fine stone is 1:1; the particle size of the coarse stone is 50-80 mesh, and the particle size of the fine stone is 120-150 mesh.

3. The method for preparing a stone material for architectural decoration according to claim 1, characterized in that: In S2, the amount of each component, by weight, is 16-25 parts of polyurethane adhesive, 50-80 parts of modified epoxy resin, 30-56 parts of epoxy resin curing agent, and 340-470 parts of mixed stone.

4. The method for preparing a stone material for architectural decoration according to claim 1, characterized in that: In step 1, the molar ratio of allylphenol, epichlorohydrin and sodium hydroxide is 1:3:(2~2.5).

5. The method for preparing a stone material for architectural decoration according to claim 1, characterized in that: In step 2, p-allylphenol glycidyl ether and 1,1,1,3,5,5,5-heptamethyltrisiloxane are mixed in a molar ratio of 1:

1.

6. The method for preparing a stone material for architectural decoration according to claim 1, characterized in that: In step 3, 5,5-dimethylhydantoin and silicone-modified p-allylphenol glycidyl ether are mixed at a molar ratio of 1:

2.

7. The building decoration stone prepared by the preparation method according to any one of claims 1 to 6.

Citation Information

Patent Citations

  • Preparation method of graphene-organic silicon synergistically enhanced polyurethane grafted modified epoxy resin

    CN116284655A

  • Ecological stone slab and preparation method thereof

    CN118652073A